Clinical assessment of demineralization and remineralization surrounding orthodontic brackets with FluoreCam - KORKUT, BORA; TAĞTEKİN, DİLEK; YANIKOĞLU, FUNDA (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2017)
Objective: To determine quantitatively the amount of demineralization and the ability of commercially available products and an experimental cream to inhibit or reverse orthodontic related demineralization. Methods: A total of 20 patients who were 25-35 years old and having orthodontic treatment for 6-8 months were chosen. Caries risk assessments were done for each patient and ones with moderate risk were included. Patients with fixed orthodontic appliances were divided into 4 groups (5 patients each) including one control and 3 study groups. All patients used same toothpaste 2 times a day during the 3 weeks study period. Additional to the toothpaste first study group used MI Paste Plus (GC, Tokyo, Japan), second study group used Remin Pro (Voco, Cuxhaven, Germany) and third group used an experimental remineralizing cream per day for 3 weeks. Maxillary central and lateral incisors of each patient were examined by FluoreCam (Daraza Therametric Technologies, USA) device. The examinations were performed at baseline and at the end of 1st, 2nd and 3rd weeks. Results: According to the FluoreCam measurements the control group showed significant amount of demineralization at the end of 3 weeks, moreover the amount of demineralization has gradually increased in time. At the end of the study all 3 study groups showed significant amount of remineralization and the amount of remineralization for all the 3 study groups has gradually increased in time. However the amount of remineralization for 3rd study group was lesser than the 1st and 2nd study groups. The remineralization amounts for the 1st and 2nd study groups were determined to be identical. Conclusions: This study demonstrated that demineralization is measurable around orthodontic brackets and the demineralization can be completely inhibited and/or reversed by the use of commercially available remineralization products.
Keywords: LIGHT-INDUCED FLUORESCENCE; WHITE SPOT LESIONS; MI PASTE PLUS; FLUORIDE VARNISH; ADJACENT; MUTANS; HONEY